2017
DOI: 10.1038/mp.2017.38
|View full text |Cite
|
Sign up to set email alerts
|

Cafeteria diet and probiotic therapy: cross talk among memory, neuroplasticity, serotonin receptors and gut microbiota in the rat

Abstract: The western diet is known to have detrimental effects on cognition and the gut microbiota, but few studies have investigated how these may be related. Here, we examined whether a probiotic could prevent diet-induced memory deficits. Rats were pre-exposed to vehicle, low or high doses of VSL#3 for 2 weeks before half were switched from chow to a cafeteria diet (Caf) for 25 days; VSL#3 treatment continued until death. High-dose VSL#3 prevented the diet-induced memory deficits on the hippocampal-dependent place t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 65 publications
4
63
0
1
Order By: Relevance
“…Similar to the changes in the expression of serotonin receptors induced by WD reported here were previously reported. For example, cafeteria and high-energy diets decreased brain expression of Htr2c receptor in rats (Lopez-Esparza et al, 2015;Beilharz et al, 2018). Mice exposed to high-fat diet displayed changes in the expression of Htr2a in the olfactory nucleus and of Htr2c in the medial amygdaloid nucleus (Huang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the changes in the expression of serotonin receptors induced by WD reported here were previously reported. For example, cafeteria and high-energy diets decreased brain expression of Htr2c receptor in rats (Lopez-Esparza et al, 2015;Beilharz et al, 2018). Mice exposed to high-fat diet displayed changes in the expression of Htr2a in the olfactory nucleus and of Htr2c in the medial amygdaloid nucleus (Huang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, minocycline has antibiotic activity and has been recently reported to reduce some effects of high-fat diet in rats through altering food intake and the gut microbiome composition 27 . Given the role of the gut microbiome in diet-induced cognitive impairment 11,28,29 , it is important to examine the effects of minocycline on microbiome composition and to investigate potential behavioral associations as these have not been previously studied.…”
Section: Introductionmentioning
confidence: 99%
“…Not only are we still trying to move past correlations and understand the complex web of causality, but there are fundamental aspects of the microbiota–gut–brain axis that we do not yet understand. For example, while manipulating the microbiota with probiotics is generally seen to have only positive (or in the worst case, negligible) outcomes for human health, some animal models have shown that probiotic treatment can produce unexpected (and possibly undesirable outcomes) on memory (Beilharz et al, ). Considering these data and the early stage of current research in the microbiota–gut–brain axis, caution is warranted in translating potential therapeutics from emerging findings.…”
Section: Clinical Implications Of Microbiota–gut–brain Axis Research?mentioning
confidence: 99%